PERSONAL VALUES IN THE STRUCTURE OF THE SOCIAL ENVIRONMENT AND PROFESSIONAL ACTIVITY - Sarancha, Iryna; Mnyshenko, Kateryna; Khilya, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article presents the results of a research on the impact of the values system of personal attitudes and values of the individual to choose a profession, as well as subsequent impact of this choice on the social environment in general. For our work, we used the following methods: pedagogical experiment, test and other methods for determining values in the structure of the personality (Methodology M. Rokeach, Sack's Sentence Completion Test, projective test methods «Tree of values», «I-real / I-ideal»).During the experiment, we also turned to the method of interviewing students (last courses of bachelor's and master's degrees) and working professionals in the educational environment to determine the impact of personal values on professional competence.We were able to determine the features of professional activity understanding of the social development needs in the educational environment, its strengths and weaknesses for the formation of the social order of the state and the individual, as well as ways to improve the social environment on the basis of the proposed forms of work with the values of a future professional.